Reflections on investment planning in the electricity and natural gas sectors: lessons and pending homework - Leyva Flores, Ricardo (2022)
In this article, the author presents an analysis of the positive and negative aspects of state planning in the electricity and natural gas sectors. In both sectors, it indicates how the planning intervention by the State has been strengthened over the years. However, it also points out the problems that it still presents.The author highlights the importance of state planning in a social market economy regime, in addition to this, he points out the problems that not have sufficient incentives to satisfy demand, since that is where the State has to intervene through public companies.Likewise, the author presents certain recommendations made by the Multisectoral Commission for the Reform of the Electricity Subsector to contribute to the problems that have been generated in various cases due to the lack of efficient state planning.